2023
DOI: 10.1186/s12903-023-02742-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral status is associated with chewing difficulty in Thai older adults: data from a National Oral Health Survey

Abstract: Background The number of older adults in Thailand is increasing. Better chewing ability is associated with healthy aging. Although numerous studies have demonstrated the relationship between social backgrounds, dental service utilization, oral status and chewing difficulty, there is no study in Thailand using national oral health data to identify the variables involved with chewing difficulty among Thai older adults. Therefore, the aim of this study was to determine the association between oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…In contrast, Perea et al, 22 found opposite results in which participants with higher education showed better OHRQoL. Furthermore, higher income was significantly associated with better OHRQoL in our sample of CD wearers which is in agreement with several studies 46–48 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, Perea et al, 22 found opposite results in which participants with higher education showed better OHRQoL. Furthermore, higher income was significantly associated with better OHRQoL in our sample of CD wearers which is in agreement with several studies 46–48 …”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, higher income was significantly associated with better OHRQoL in our sample of CD wearers which is in agreement with several studies. [46][47][48] Receiving dental treatment at a private or governmental clinic/ hospital had no significant relationship with OHRQoL in the present study. The majority of participants (85.7%) were treated at governmental clinics which may be the reason for this lack of significant difference.…”
Section: Methods Of Cleaning N (%)mentioning
confidence: 79%
“…Gender, age, family income level, family size, number of natural teeth, and selfperceived oral health status (SPOHS) were considered as covariates [10,12,13,33]. There were two gender groups, 'male' and 'female', and two age groups, '65-74' and '75+'.…”
Section: Covariatesmentioning
confidence: 99%
“…Regarding SPOHS, participants were asked about their perception of their dental health: "When you think about yourself, how do you feel about your oral health, including your teeth and gums?" Possible responses included 'very good,' 'good,' 'moderate,' 'bad,' or 'very bad' [13,33].…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation